Factores influyentes y determinación de la resistencia del hormigón in situ, utilizando método de giro. - Najarbashi, Pooria; Naderi, Mahmoud (Innovaciencia, 2019)
Concrete strength represents by far the most critical property of concrete. It represents the mechanical properties of concrete. On-site evaluation of concrete strength remains the fundamental challenge in the condition assessment of existing infrastructure. Although standard laboratory methods can be typically used but most of these testing methods are costly and time-consuming. Among the in-situ methods, the “twist-off ” method with very slight damage is genuinely a convenient, fast and also low-cost technique that provides accurate results for engineers. In this study, the twist-offmethod has been used for the assessment of in-situ strength of the 30 concrete structures in Qazvin in Iran. The results showed structures studied had a strength of 45 to 600 kg/cm2 and the average is about 200 kg/cm2. The observed variation is very high, as well as a significant difference between the compressive strength of the columns, and the floors of the buildings that all indicate non-standard concrete mixing and inadequate control over construction. However, according to the past experience and results of the samples, some recommendations in this regard have been suggested.